Biomechanical Analysis of the Ross Procedure in an Ex Vivo Left Heart Simulator. Issue 2 (March 2022) - Bryan, Amelia Y.; Brandon Strong, E.; Kidambi, Sumanth; Gilligan-Steinberg, Shane; Bennett-Kennett, Ross; Lee, James Y.; Imbrie-Moore, Annabel; Moye, Stephen C.; Hendrickx-Rodriguez, Sebastian; Wang, Hanjay; Dauskardt, Reinhold H.; Joseph Woo, Y.; et al.
Background: Neo-aortic pulmonary autografts often experience root dilation and valve regurgitation over time. This study seeks to understand the biomechanical differences between aortic and neo-aortic pulmonary roots using a heart simulator. Methods: Porcine aortic, neo-aortic pulmonary, and pulmonary roots (n = 6) were mounted in a heart simulator (parameters: 100 mm Hg, 37 °C, 70 cycles per minute, 5.0 L/min cardiac output). Echocardiography was used to study root distensibility (percentage change in luminal diameter between systole and diastole) and valve function. Leaflet motion was tracked with high-speed videography. After 30 min in the simulator, leaflet thickness (via cryosectioning), and multiaxial modulus (via lenticular hydrostatic deformation testing) were obtained. Results: There were no significant differences between aortic and neo-aortic pulmonary leaflet motion, including mean opening velocity (218 vs 248 mm/s, P = .27) or mean closing velocity (116 vs 157 mm/s, P = .12). Distensibility was similar between aortic (8.5%, 1.56 mm) and neo-aortic pulmonary (7.8%, 1.12 mm) roots ( P = .59). Compared to virgin controls, native pulmonic roots exposed to systemic pressure for 30 min had reduced leaflet thickness (630 vs 385 µm, P = .049) and a reduced Young's modulus (3, 125 vs 1, 089 kPa, P = .077). In contrast, the aortic roots exposed to pressure displayed no significant difference in aortic leaflet thickness (1, 317 vs 1, 256 µm, P = .27) or modulus (5, 931 vs 3, 631 kPa, P = .56). Conclusions: Neo-aortic pulmonary roots demonstrated equivalence in valve function and distensibility but did experience changes in biomechanical properties and morphology. These changes may contribute to long-term complications associated with the Ross procedure.